Hubungan Antara Dukungan Keluarga Dengan Kepatuhan Diet Pada Penderita Diabetes Mellitus Tipe 2 Di Rw 15 Wilayah Kerja Puskesmas Cimahi Utara - Argi, Argi Virgona Bangun; Galih, Galih Jatnika; Herlina, Herlina (JURNAL KESEHATAN KARTIKA, 2019)
Diabetes mellitus (DM) is a chronic disease where blood sugar levels (glucose) accumulateand exceed normal values. Diabetes mellitus divided into 2 type. Type 1 diabetes and type 2diabetes, while the most common type of diabetes mellitus is diabetes type 2. About 90-95%of patients suffer from diabetes mellitus type 2. There are several management of diabetesmellitus one of them is diet management. Family support is one of the factors that supportpeople with diabetes mellitus to obedient with their diet. The purpose of this research was toperceive the relationship between family support and dietary compliance in patients with type2 diabetes melittus in working area of community center 15 North Cimahi. The method usedis a correlation design using a cross sectional approach. The population in this research was48 respondents of type 2 diabetes mellitus in working area of community center 15 NorthCimahi. The sampling technique used in this study was total sampling with a sample of 48patients. The instruments used in family support was the Hensarling Diabetes Family SupportScale (HDFSS) and dietary compliance instrument was Perceived Dietary Adherencequestionnaire (PDAQ). Analysis of the data used in this research is univariat with normaldistribution of familly support is 66 (Mean), compliance diet is 23 (Mean) and bivariat is chisquare. Based on the results of this research, the results of good family support withadherence to a compliant diet (73.9%) and poor family support with non-adherent dietarycompliance (60.0%). The results showed a significant relationship between family supportand dietary compliance in type 2 diabetics in the working area of Community Center 15North Cimahi with a p value of 0.038. Advice for people with diabetes mellitus to practice orapply the diabetes mellitus diet to control blood sugar levels and prevent complications.